The riodinid taxa described by Rudolf Emil Mell (Lepidoptera, Papilionoidea, Riodinidae), with notes on related ones - Huang, Si-Yao; Inayoshi, Yutaka; Léger, Théo; Espeland, Marianne (Zootaxa, 2024)
The two riodinid taxa described by Rudolf Emil Mell were reviewed. Lectotypes have been designated for Sospita sobrina Mell, 1923 and Hipporion chauchowensis Mell, 1923. Abisara freda Bennett, 1957 syn. n. and A. freda daliensis Sugiyama, 1992 syn. n. are synonymized with A. sobrina (Mell, 1923) and Polycaena chauchowensis pallidior Forster, 1951 syn. n. is synonymized with P. chauchowensis (Mell, 1923). The adult and genitalia of the lectotypes and related specimens of the aforementioned taxa are illustrated.